Anatomical and Functional Results of Lamellar Macular Holes Surgery - Papadopoulou, D.; Donati, G.; Mangioris, G.; Pournaras, C. J. (Klinische Monatsblätter für Augenheilkunde, 2016)
Purpose: To determine the long-term surgical findings and outcomes after vitrectomy for symptomatic lamellar macular holes. Methods: We studied 28 patients with lamellar macular holes and central visual loss or distortion. All interventions were standard 25 G vitrectomy with membranectomy of the internal limiting membrane (ILM), peeling and gas tamponade with SF6 20 %. Operations were performed by a single experienced surgeon within the last 3 years. Best corrected visual acuity and optical coherence tomography appearance were determined preoperatively and postoperatively. Results: Following the surgical procedure, all macular holes were closed; however, in 3 eyes, significant foveal thinning was associated with changes in the retinal pigment epithelium changes. The mean best-corrected visual acuity improved postoperatively in the majority of the patients (n: 21, mean 0.3 logMAR), stabilised in 4 patients and decreased in 3 patients (mean 0.4 logMAR). Spectral Domain-Optical coherence tomography (SD-OCT) showed resolution of the lamellar lesion and improved macular contour in all cases. Conclusion: We demonstrated improvement in postoperative vision and the anatomical reconstruction of the anatomical contour of the fovea in most eyes with symptomatic lamellar holes. These findings indicate that vitrectomy, membranectomy and ILM peeling with gas tamponade is a beneficial treatment of symptomatic lamellar macular holes.
Keywords: lamellar macular hole; vitrectomy; epiretinal membrane